Quagmire : nation-building and nature in the Mekong Delta - Biggs, David A. (Weyerhaeuser environmental book., 2010)
"In the twentieth century, the Mekong Delta emerged as one of Vietnam's most important economic regions. Its swamps, marshes, creeks, and canals played a major role in Vietnam's turbulent past, from the struggles of colonialism, to the the Cold War, and to the present day. [This book] considers these struggles, their antecedents, and their legacies from the perspective of environmental history."--Cover leaf